Perubahan Politik dan Rent Seeking Activities [Changes in Political and Rent-Seeking Activities] - Ignatius Ismanto (Universitas Pelita Harapan, 2017)
The economic crisis that hit Indonesia both in mid-1980s and 1997 has allowed Indonesia to liberalize its economy. Economic liberalization has promoted a deeping of Indonesia’s economic integration into the global capitalist economy. The economic crisis in 1997 not only challanged the economy. The crisis also caused a flourishing of political change: the delegitimizing of an authoritarian regime, the spreading of political liberalization, and the burgeoning of democratization. Decentralization has been adopted as a deepening instrument in promoting democracy. Political pressure for curbing rent seeking activities has been articulated along with the country’s changing economy. Ironically, political liberalization that overhauled the authoritarian structure and power has failed to keep rent seeing activities in check. Rent seeking activities have institutionalized following the country’s changing economy and, therefore, they have been vulnerable to corruption.